Impact of lenvatinib-induced proteinuria and renal dysfunction in patients with thyroid cancer - Shibutani, Yuma; Suzuki, Shinya; Sagara, Atsunobu; Enokida, Tomohiro; Okano, Susumu; Fujisawa, Takao; Sato, Fumiaki; Yumoto, Tetsuro; Sano, Motohiko; Kawasaki, Toshikatsu; Tahara, Makoto (Frontiers in Oncology, 2023)
Background Proteinuria is the most frequent adverse event of lenvatinib use. However, the association between lenvatinib-induced proteinuria and renal dysfunction remains unclear. Methods We retrospectively reviewed medical records of patients with thyroid cancer without proteinuria treated with lenvatinib as a first-line systemic therapy at the initiation of treatment to assess the association between lenvatinib-induced proteinuria and renal function and the risk factors for the development of ≥3+ proteinuria on a dipstick test. Proteinuria was assessed by the dipstick test throughout the treatment in all cases. Results Of the 76 patients, 39 developed ≤2+ proteinuria (low proteinuria group) and 37 developed ≥3+ proteinuria (high proteinuria group). There was no significant difference in estimated glomerular filtration rate (eGFR) between high and low proteinuria groups at each time point, but there was a trend toward a significant decrease in eGFR of -9.3 ml/min/1.73 m2 in all patients after 2 years of treatment. The percentage of change in eGFR (ΔeGFR) significantly decreased in the high proteinuria group compared to that in the low proteinuria group (ΔeGFR: -6.8% vs. -17.2%, p=0.04). However, there was no significant difference in development of severe renal dysfunction with eGFR <30 ml/min/1.73 m2 between the two groups. Moreover, no patients permanently discontinued treatment because of renal dysfunction in both groups. Furthermore, renal function after completion of lenvatinib was reversible. Conclusions There was no association between the degree of lenvatinib-induced proteinuria and renal function. Therefore, treatment should be continued with attention to renal function, regardless of the degree of proteinuria.